(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
T.S. Eliot, at the beginning of this essay, writes that the word “tradition” is generally used in a pejorative sense in English. We (the English) generally think that the term “traditional”, in the context of art and literature, means zero innovation and no originality. English people unnecessarily label French as “more critical” and “less spontaneous” and think about themselves as innovative and original. The English seem to give more importance to the individual peculiarities of a writer and think that it is better if he/she does not resemble others. We (the English) take pride in the belief that we write more freely and spontaneously. But we seem to forget that “criticism is as inevitable as breathing.”(Eliot) We generally think that a poet should be completely different from his predecessors (especially his immediate predecessors) and naively believe that this difference is the only proof of his/her original genius. But if we remove this prejudice of ours we will find “that not only the best, but the most individual parts of his work may be those in which the dead poets, his ancestors, assert their immortality most vigorously.”(Eliot) This is how Eliot relates “tradition” with “individual talent”. Tradition for him does not mean blind following and slavish imitation. It is a broad concept. Tradition involves historical sense, i.e., “a perception, not only of the pastness of the past, but of its presence.”(Eliot) Past has a complete relevance in the present. “The historical sense compels a man to write not merely with his own generation in his bones, but with a feeling that the whole of the literature of Europe from Homer and within it the whole of literature of his own country has a simultaneous existence and composes a simultaneous order. This historical sense, which is a sense of the timeless as well as of the temporal and of the timeless and of the temporal together, is what makes a writer traditional.”(Eliot) In the words of Hans Heinz Holz: “Genuine tradition is a dialectical phenomenon: in it we grasp hold of what has been as being something else, which while being something else is at the same time our own and nothing but our own.”(Holz 78)